Sex Differences in Clinical Parameters, Pharmacological and Health-Resource Utilization in a Population With Hypertension Without a Diagnosis of COVID-19 - Ana Lear-Claveras; Bárbara Oliván-Blázquez; Bárbara Oliván-Blázquez; Bárbara Oliván-Blázquez; Ana Clavería; Ana Clavería; Ana Clavería; Sabela Couso-Viana; Sabela Couso-Viana; Jesús Puente-Comesaña; Jesús Puente-Comesaña; Rosa Magallón Botaya; et al. (Frontiers Media S.A., 2022)
Objectives: Determine the changes in clinical, pharmacological and healthcare resource use parameters, between the 6 months prior to the lockdown and the 6 months following its end, in a population with hypertension who did not have a diagnosis of COVID-19.Methods: Real world data observational study of 245,979 persons aged >16 years with hypertension in Aragon (Spain). Clinical (systolic-diastolic blood pressure, estimated glomerular filtration rate (eGFR), blood creatinine, cholesterol, triglycerides and anthropometric measures); pharmacological (diuretics, calcium channel antagonists, and ACE inhibitors); and utilization of healthcare resources were considered. We performed the Student's T-test for matched samples (quantitative) and the Chi-squared test (qualitative) to analyze differences between periods.Results: SBP, DBP, parameters of renal function and triglycerides displayed a significant, albeit clinically irrelevant, worsening in women. In men only DBP and eGFR showed a worsening, although to a lesser extent than in women. Certain antihypertensive drugs and health-resource utilization remained below pre-pandemic levels across the 6 months post-lockdown.Conclusion: Changes in lifestyles, along with difficulties in access to routine care has not substantially compromised the health and quality of life of patients with hypertension.